An Aromatic Hydroxyamide Attenuates Multiresistant Staphylococcus aureus Toxin Expression. Issue 5 (8th January 2016) - Vomacka, Jan; Korotkov, Vadim S.; Bauer, Bianca; Weinandy, Franziska; Kunzmann, Martin H.; Krysiak, Joanna; Baron, Oliver; Böttcher, Thomas; Lorenz‐Baath, Katrin; Sieber, Stephan A.
Abstract: Methicillin‐resistant Staphylococcus aureus (MRSA) causes severe infections with only few effective antibiotic therapies currently available. To approach this challenge, chemical entities with a novel and resistance‐free mode of action are desperately needed. Here, we introduce a new hydroxyamide compound that effectively reduces the expression of devastating toxins in various S. aureus and MRSA strains. The molecular mechanism was investigated by transcriptome analysis as well as by affinity‐based protein profiling. Down‐regulation of several pathogenesis associated genes suggested the inhibition of a central virulence‐related pathway. Mass spectrometry‐based chemical proteomics revealed putative molecular targets. Systemic treatment with the hydroxyamide showed significant reduction of abscess sizes in a MRSA mouse skin infection model. The absence of resistance development in vitro further underlines the finding that targeting virulence could lead to prolonged therapeutic options in comparison to antibiotics that directly address bacterial survival. Abstract : Disarming MRSA : A new hydroxyamide compound effectively reduces the expression of devastating toxins in various S. aureus and MRSA strains. The molecular mechanism was investigated by transcriptome analysis, as well as by affinity‐based protein profiling. Systemic treatment with the hydroxyamide showed significant reduction of abscess sizes in an MRSA mouse skin infection model.